Are Leukocyte Esterase (LE) strip and Alpha-Defensin kit reliable enough to diagnose peri-prosthetic joint infection, intra-operatively? - Usman Nazir Gill; Adeel Hamid; Shuja Uddin; Naveed Ali Shair; Muhammad Qasim; Muhammad Hanif Mian; Irfan Mehboob (Rheumatica Acta: Open Access - Peertechz Publications, 2022)
Background: Despite improvement in sterilization techniques, peri-prosthetic joint infection (PJI) is the most fearsome complication after hip and knee arthroplasties. Various strategies have been devised from time to time to diagnose and treat PJI. Recently, Leukocyte esterase and alpha-defensin are identified as markers of active infection in synovial fluid. Therefore, kits are designed to detect these two markers during surgery. If found reliable, these tests will increase the confidence of surgeons in situations, where the diagnosis of PJI is not established. Material and methods: This study was conducted on 132 patients in Lahore General Hospital; from August 2020 to December 2021. Leukocyte Esterase strip and Alpha-Defensin kit were used to detect infection in synovial samples taken just before performing arthrotomy, intra-operatively. Patients were divided into 2 groups, Group-A had 31 patients with peri-prosthetic joint infection (PJI) diagnosed as per Musculoskeletal Infection Society (MSIS) criteria, whereas in Group B 101 patients were present in whom PJI was not present. Synovial tissue and fluid samples were also sent to a laboratory for culture and histopathology; so that sensitivity and specificity of LE strips and Alpha-Defensin Kits could find out. Results: The mean age of patients in our study was 59.6 SD 11.90 years with a male to female ratio of 85:47. 31 patients were diagnosed as PJI after primary hip or knee arthroplasty based on serological investigations and culture of joint aspiration. The sensitivity and specificity of LE strips were 90.32% and 95.04%, whereas that of Alpha defensin was 93.54% and 100% respectively. The correlation coefficient between the LE strip test and synovial fluid polymorphonuclear neutrophils (PMN) counts was 0.811 and it was even higher when the Alpha-Defensin kit was used (0.845). Conclusion: Both LE and Alpha-Defensin kits are highly specific and sensitive in diagnosing PJI. Though Alpha-defensin is more accurate the cost-effectiveness of the LE strip makes it a more feasible option in diagnosing PJI, intra-operatively.